Earnings quality: Investment opportunity set and corporate governance as intervening variable - Erawati, Teguh; Widyastuti, Anita (Proceeding International Conference on Accounting and Finance, 2024)
Purpose: This research intends to test the influence amongst investment opportunity set and earnings quality with corporate governance as an intervining variable. This research is important to obtain new information or discoveries. This research can be said to be new research because the researchers modified the research model by using intervining. Metode: This research is using a quantitative approach. The sampling model uses purposive sampling with certain criteria. From 35 samples of manufacturing companies, 143 data were obtained. To analyze this research data using descriptive statistical testing, classical assumption testing, hypothesis testing and intervening testing sobel test. Results: This research reveals that investment opportunity set have a negative effect on earnings quality. Corporate governance has a negative effect on earnings quality. Investment opportunity set has a negative effect on corporate governance. And investment opportunity set has a effect on earnings quality through corporate governance as an intervining variable. Novelty: This research can be said to be renewal research because it uses a new model by adding an intervining variable, namely corporate governance. The existence of corporate governance can test whether the independent variable investment opportunity set has an effect on the dependent variable earnings quality through corporate governance as an intervening variable